Incidence and management of intraoperative complications during small‐incision lenticule extraction in 3004 cases. Issue 6 (June 2017) - Wang, Yan; Ma, Jiaonan; Zhang, Jiamei; Dou, Rui; Zhang, Hui; Li, Liuyang; Zhao, Wei; Wei, Pinghui
Abstract : Purpose : To assess the intraoperative complications during small‐incision lenticule extraction (SMILE) for myopia and myopic astigmatism correction and evaluate visual outcomes 6 months postoperatively. Setting : Tianjin Eye Hospital, Tianjin, China. Design : Retrospective case series. Methods : Patients who had small‐incision lenticule extraction surgery were examined 1 day, 7 days, 1 month, 3 months, and 6 months postoperatively. Demographic characteristics, visual outcomes, and intraoperative complications were recorded. Moreover, the incidence and management of the complications and the potential factors were analyzed. Results : Of the 3004 eyes (1511 patients), 134 (4.46%) had intraoperative complications, including suction loss (28 cases [0.93%]), incisional bleeding (28 cases [0.93%]), opaque bubble layer (22 cases [0.73%]), subconjunctival hemorrhage (20 cases [0.67%]), black areas (10 cases [0.33%]), unintended posterior plane dissection (10 cases [0.33%]), tearing of the lenticule (8 cases [0.27%]), abrasion at the incision (5 cases [0.17%]), and inaccurate laser pulse placement due to eye movement (3 cases [0.10%]). The complications were resolved instantaneously using appropriate management procedures; all cases had good visual outcomes. Six months postoperatively, 99.80% of cases had an uncorrected distance visual acuity better than 20/25 and the mean corrected distance visual acuity was −0.06 logarithm of the minimum angle of resolution ± 0.07 (SD). Conclusions : Although small‐incision lenticule extraction shows promising outcomes for correction of myopia and myopic astigmatism, intraoperative complications still inevitably occur. However, satisfactory visual outcomes may be achieved using appropriate management techniques.